2022
DOI: 10.1002/ajh.26781
|View full text |Cite
|
Sign up to set email alerts
|

Venetoclax and hypomethylating agent therapy in myelodysplastic syndromes: Big picture perspective

Abstract: The importance of the biological and clinical continuum of myelodysplastic syndromes (MDS) and acute myeloid leukemia (AML) was officially acknowledged through the designation of the MDS/AML category in the International Consensus Classification (ICC) of Mye-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Recently, it was reported that the combination of HMA (azacitidine) with venetoclax in high-risk MDS might lead to a higher response rate. The combination of HMA and venetoclax was approved for high-risk MDS patients ineligible for allo-SCT [ 106 ].…”
Section: Treatment Of Myelodysplastic Neoplasmmentioning
confidence: 99%
“…Recently, it was reported that the combination of HMA (azacitidine) with venetoclax in high-risk MDS might lead to a higher response rate. The combination of HMA and venetoclax was approved for high-risk MDS patients ineligible for allo-SCT [ 106 ].…”
Section: Treatment Of Myelodysplastic Neoplasmmentioning
confidence: 99%